INTERPRETASI NCTZEN MENGENAI CITRA NCT DALAM POSTINGAN GOYANG MENDUNG TANPO UDAN - Anjasmoro Dwi Pamungkas; Dholley Dwi Jatmiko Latabulo (Jurnal Pustaka Komunikasi, 2023)
The image needs to be built and formed in various ways. This is motivated by the desire of all companies to always maintain a positive image in the eyes of the public. Because for them, image is one of the essential factors for a brand or company to survive and be recognized by the wider community. Likewise, NCT Dream builds an image of NCTzen Indonesia through the Goyang Mendung Tanpo Udan post. This study aims to determine how NCTzen's interpretation of NCT's image in the Goyang Mendung Tanpo Udan post on NCT Dream's official Instagram. Researchers used Stuart Hall's encoding-decoding theory. In this study, researchers used the audience reception analysis method. The results of this study indicate that one informant falls into the negotiation category because the post contains popularity and also follows the growing trend. Four informants fall into the opposition category because the post does not only contain popularity. This is motivated and dominated by differences in the length of time the informant has been an NCTzen.